Esoteric decision-making: Judicial responses to the judicialisation of politics, the Constitutional Court and EFF II. Issue 4 (1st October 2020) - Gildenhuys, Lauren
Abstract: Esoteric decision-making refers to the express reliance on apolitical, technical and legal justifications to substantiate a judicial outcome that is preferred for political reasons, which remain unexpressed. Historically, the Constitutional Court has, in the face of highly political cases, relied on a number of esoteric decision-making techniques. These include prevailing on narrow or apolitical sources of law; using technical, formalist modes of reasoning; and exploiting the indeterminism of the separation of powers. Esoteric decision-making may be a necessary and justified judicial response to instances of the judicialisation of politics in order to protect the institutional security, independence and legitimacy of courts. However, when used ineptly, it risks inviting the institutional vulnerability that its use seeks to avoid. To illustrate this point, this paper discusses the majority judgment in EFF II and contrasts it to previous instances in which the Court has applied esoteric decision-making more successfully. Given the prevalence of the judicialisation of politics in South Africa, the Constitutional Court's continued institutional legitimacy will depend on the careful and strategic application of esoteric decision-making in future cases.